Proton Pump Inhibitor and Tacrolimus Uses are Associated With Hypomagnesemia in Connective Tissue Disease: a Potential Link With Renal Dysfunction and Recurrent Infection - Hanaoka, Hironari; Kikuchi, Jun; Kaneko, Yuko; Seki, Noriyasu; Tsujimoto, Hideto; Chiba, Kenji; Takeuchi, Tsutomu (Frontiers in Pharmacology, 2021)
Background: Low levels of serum magnesium perturb renal tubular cell function and lymphocytes, resulting in renal deterioration and an imbalance in mononuclear cells. This study investigated the mechanism and influence of hypomagnesemia in patients with connective tissue disease. Methods: We retrospectively evaluated patients with connective tissue disease and available serum magnesium data who visited Keio University Hospital in 2019. Patients were divided into two groups: those with (serum magnesium <1.8 mg/dL) and those without hypomagnesemia; their rates of hospitalization for severe infection and cumulative renal deterioration were compared. Patients’ fractions of lymphocytes and natural killer and dendritic cell subsets, as measured by fluorescence-activated cell sorting (FACS) analysis, were also compared. Results: Among 284 patients, hypomagnesemia was detected in 63 (22.2%). Multivariate analysis revealed that the use of proton pump inhibitors (odds ratio [OR], 1.48; p = 0.01) and tacrolimus (OR, 6.14; p < 0.01) was independently associated with hypomagnesemia. In addition, the renal deterioration rate was significantly higher in tacrolimus and/or proton pump inhibitor users with hypomagnesemia (p = 0.01). The hospitalization rate for severe infection was also higher in patients with hypomagnesemia (p = 0.04). FACS analysis showed lower CD8+ T cell, CD19+ B cell, natural killer cell, and dendritic cell counts in patients with hypomagnesemia (p = 0.03, p = 0.02, p = 0.02, and p = 0.03, respectively). Conclusions: The use of tacrolimus and proton pump inhibitors may be associated with hypomagnesemia and lead to poor renal outcomes and severe infection in patients with connective tissue disease.